Dielectric Characterization and Separation Optimization of Infiltrating Ductal Adenocarcinoma via Insulator-Dielectrophoresis - Adekanmbi, Ezekiel O. (Micromachines (Basel), 2020)
The dielectrophoretic separation of infiltrating ductal adenocarcinoma cells (ADCs) from isolated peripheral blood mononuclear cells (PBMCs) in a ~1.4 mm long Y-shaped microfluidic channel with semi-circular insulating constrictions is numerically investigated. In this work, ADCs (breast cancer cells) and PBMCs’ electrophysiological properties were iteratively extracted through the fitting of a single-shell model with the frequency-conductivity data obtained from AC microwell experiments. In the numerical computation, the gradient of the electric field required to generate the necessary dielectrophoretic force within the constriction zone was provided through the application of electric potential across the whole fluidic channel. By adjusting the difference in potentials between the global inlet and outlet of the fluidic device, the minimum (effective) potential difference with the optimum particle transmission probability for ADCs was found. The radius of the semi-circular constrictions at which the effective potential difference was swept to obtain the optimum constriction size was also obtained. Independent particle discretization analysis was also conducted to underscore the accuracy of the numerical solution. The numerical results, which were obtained by the integration of fluid flow, electric current, and particle tracing module in COMSOL v5.3, reveal that PBMCs can be maximally separated from ADCs using a DC power source of 50 V. The article also discusses recirculation or wake formation behavior at high DC voltages (>100 V) even when sorting of cells are achieved. This result is the first step towards the production of a supplementary or confirmatory test device to detect early breast cancer non-invasively.